Engineering Chlorella-based consortia for sustainable food wastewater treatment: nutrient recovery, pollutant degradation and advanced harvesting - Lin Zhao; Shujie Wei; Yifan Zhang; Luguang Tao; Yuwei Xu; Yiming Wang; Zhangli Hu; Jun Tang; Song Wang (Environmental Research, 2026)

A sulfonate-rich gel electrolyte enables coupled polyiodide confinement and Zn2+ transport regulation for durable aqueous ZnI2 batteries - Qing Luo; Ling Wang; Simin Chai; Yuwei Li; Xin Lin; Jinpeng Guan; Zetao Chen; Caifeng Li; Na Li; Lin Zeng; Jianxiong Xu (Chemical Engineering Journal, 2026)

ABA-dependent priming of stomatal immunity by the harpin protein PopW restricts entry of Xanthomonas euvesicatoria in tomato - Xiaosi Zhou; Tian Wei; Yuwei Xue; Jiangfei Hu; Yuqing Lin; Lina Xu; Hongwei Zhao; Hongxia Liu (Plant Science, 2026)

Thermal evolution of biomarker profiles in the Ordovician biodegraded reservoirs of the Tabei Uplift, Tarim Basin, northwestern China: implications from closed-system thermal simulation experiments - Yuwei Yang; Yuhong Liao; Yijun Zheng; Yueyi Huang; Bin Cheng; Huanyu Lin; Yunpeng Wang; Ping’An Peng (Journal of Asian Earth Sciences, 2026)

Mapping recorded illegal tree-felling intensity for forest-governance screening in China: Evidence from court verdicts and interpretable spatial machine learning - Lin Chen; Yuwei Hong; Yu Liu; Mengxue Yuan; Ximing Quan; Weixing Xue; Pujie Wei; Yingjie Liao; Zhaogui Yan (Forest Policy and Economics, 2026)

Axial oxygen–coordinated niobium single-atom catalyst enables durable bifunctional oxygen reduction/evolution electrocatalysis in zinc–air batteries - Xueyan Lin; Ngoc Thanh Ngan Thai; Yuwei Zhu; Haiyan Tan; Rishav Baranwal; Linqin Mu; Arunachala Mada Kannan; Jingyue Liu; Bin Wang; Zhaoyang Fan (Chemical Engineering Journal, 2026)

MAF-UNet: A multimodal attention fusion U-Net for automatic loess sinkhole detection and mapping - Fangjie Tian; Lin Wang; Sheng Hu; Fanyu Zhang; Ninglian Wang; Yuwei Wu; Xingang Wang (Engineering Geology, 2026)

Chemical Characteristics, Sources, and Transport Pathways of PM2.5 in a Mid-Altitude Industrial City of the Upper Yellow River Basin - Lin Yi; Juanjuan Qin; Yuanyuan Qin; Yuwei Gao; Jingnan Li; Xiaoying Su; Shuming Zhang; Zhiguo Rao; Jihua Tan; Peng Yi (Water, Air, & Soil Pollution, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

Management regimes underpin soil carbon accrual following forest conversion to tea plantations across China - Lin Chen; Li Ruan; Yu Duan; Biao Feng; Yixuan Bai; Scott X. Chang; Teng Yang; Yowhan Son; Yuwei Yuan; Shangwen Fu; Chuan Yue; Zhongyi Li; et al. (Science Bulletin, 2026)

Atmospheric new particle formation from sulfuric acid-amine nucleation in a rural area of the North China Plain - Yiliang Liu; Yiqun Lu; Gan Yang; Chuang Li; Yuwei Wang; Runlong Cai; Lei Yao; Yang Chen; Lin Wang (Journal of Environmental Sciences, 2026)

Corrigendum to “Simultaneous nitrogen and phosphorus removal from low carbon-to-nitrogen ratio wastewater using an inorganic multi-electron donor autotrophic denitrification (MEDAD) biofilter: Feasibility, performance, and mechanisms” [J. Environ. Chem. Eng., 13:5 (2025) 119015] - Lin Zhao; Yifan Zhang; Yuwei Xu; Jun Tang (Journal of Environmental Chemical Engineering, 2026)

Efficient beneficiation mechanism of Microemulsion-Enhanced fine coal Particles: Synergizing dispersion and collision - Yuwei Qin; Xiaodong Li; Chenwei Li; Guangshan Liu; Lin Li; Xiaokang Yan; Jianguo Zhang; Haijun Zhang (Fuel, 2026)

Observational characteristics of cloud-radiation-precipitation during 2019 drought period in Yunnan of Southwest China - Yuwei Tan; Xinqiang Zhou; Bing Chen; Jiandong Li; Guo Lin; Xiaohong Liu; Tao Luo (Climate Dynamics, 2026)

Low-intensity ultrasound enhances lipid biosynthesis in algae-bacteria consortia and improves symbiotic system stability in wastewater treatment - Yuwei Zhang; Yilin Zhou; Hongjun Lin; Leihong Zhao; Mingyi Ying; Meijia Zhang (Journal of Environmental Chemical Engineering, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

Magnetic aptasensor with UiO-MOFs-mediated orientation-ordered aptamers for sensitive portable test of okadaic acid toxin - Qing'ai Chen; Yuwei Zhou; Guobin Huang; Chenchen Lin; Xucong Lin (Analytica Chimica Acta, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

The whole genome sequence of Cordyceps cicadae — an edible and potential medicinal fungus - Yuwei Liu; Xueqian Li; Yiqi Meng; Yifan Wu; Yuting Jin; Xiaotong Ma; Wei Zhou; Yuchong Tan; Fu-Cheng Lin; Hongkai Wang (Molecular Genetics and Genomics, 2025)

Carboxymethyl chitosan-based form-stable phase change materials with ultra-low leakage and excellent low-temperature buffering performance - Dengshuang Guo; Yuwei Zhang; Kuncong Chen; Shun Wang; Zhongfeng Tang; Baofeng Lin (Carbohydrate Polymers, 2025)

Effects of compound probiotics on intestinal and liver transcriptome, immunity and disease resistance of zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Yiman Chen; Zhiting Zuo; Xianshan Lin; Qiaoyi Chen; Along Gao; Zhide Yu; Chong Han; Hu Shu (Aquaculture, 2025)

Simultaneous nitrogen and phosphorus removal from low carbon-to-nitrogen ratio wastewater using an inorganic multi-electron donor autotrophic denitrification (MEDAD) biofilter: Feasibility, performance, and mechanisms - Lin Zhao; Yifan Zhang; Yuwei Xu; Jun Tang (Journal of Environmental Chemical Engineering, 2025)

Characteristics of atmospheric reduced-sulfur compounds at a suburban site of Shanghai - Kai Deng; Juntao Huo; Yuwei Wang; Lihong Wang; Sijia Yin; Chuang Li; Yueyang Li; Gan Yang; Lei Yao; Qingyan Fu; Lin Wang (Journal of Environmental Sciences, 2025)

Target mitochondrial pyroptosis with sequential delivery of nanoliposomes to alleviate secondary injury following traumatic brain injury - Yuwei Lin; Jiaqi Jin; Qingyi Han; Diancheng Hang; Zijun Chen; Suihan Ye; Qing Guo; Xuyang Huang; Jinna Li; Hengzhu Zhang; Xuefeng Zhang; Yufu Zhu (Chemical Engineering Journal, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

Glycerol-driven optimization of algae-bacteria symbiosis systems for enhanced lipid production and self-flocculation - Yuwei Zhang; Jiaheng Teng; Jiahui Huang; Liguo Shen; Hongjun Lin; Renjie Li; Xiang Cai; Zeqiong Xu; Meijia Zhang (Journal of Environmental Chemical Engineering, 2025)

Homemade isothermal amplification-initiated Cas14a assay for rapid quantitative detection of aquatic RNA virus gene with no PAM - Xiufen Yang; Lin Lu; Yanchi Luo; Qingwei Wang; Jianing Wang; Yihua Ren; Yuwei Wu; Masoud Negahdary; Khaydar E. Yunusov; Sherzod A. Yuldoshov; Abdushkur A. Sarimsakov; Haimei Mao; et al. (Aquaculture, 2025)

Effects of hypoxia and reoxygenation on energy metabolism, immune response, and apoptosis in orange-spotted grouper (Epinephelus coioides) - Yuxin Wu; Yiran Lin; Bing Lin; Yukun Huang; Zhide Yu; Yonghao Ma; Yuwei Feng; Qiaoyi Chen; Along Gao; Hu Shu (Frontiers in Marine Science, 2024)
Hypoxia is an unfavorable environmental condition that produces diverse negative effects in fish. High-density cultures of Epinephelus coioides are more likely to experience hypoxic conditions than those in natural environments. To assess the effects of hypoxia on E. coioides , we examined the related enzyme activities and gene expression after 48 h of hypoxia and 24 h of dissolved oxygen (DO) recovery. Under hypoxic stress (DO: 1.2 ± 0.1 mg/L), the energy supply mode of fish changed from aerobic metabolism to anaerobic metabolism, and the serum glucose content and lactate dehydrogenase activity were significantly upregulated. Total protein, hepatic glycogen, and two key regulatory enzymes (i.e., hexokinase and pyruvate kinase) were differentially expressed in the liver, and mRNA expression of three genes (i.e., LDHA , GLUT1 , and MCT2 ) also showed a high expression trend. In serum, three immune-related enzymes (i.e., alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were found to be involved in regulation by hypoxia and showed different levels of changing patterns. Expression of inflammatory genes (i.e., IL-8 , IFNγ , MyD88 , and NF-kB ) were significantly regulated in liver. With prolongation of hypoxic stress, high expression of apoptotic genes (i.e., p53 , Bax , Bcl-2 , and Caspase-9 ) was closely related to the degree of apoptosis in the liver. Our investigation of the changes in energy metabolism, immune response, and apoptosis of E. coioides under hypoxia and reoxygenation (DO, 6.0 ± 0.1 mg/L) provides a theoretical bases for healthy aquaculture and selection of varieties with tolerance to hypoxia.

The effect of pH shifting on the calcium-fortified milk analogue with chickpea protein - Junrong Liao; Zonglin Guo; Jiahai Shen; Xiaoqing Lin; Yuwei Wang; Wanqing Yuan; Christelle Turchiuli; Yuwei Li; Yijing Zhang; Jie Lin; Hua Zheng; Song Miao; et al. (Food Chemistry, 2024)

Transformation of p-arsanilic acid by dissolved Mn(III) and enhanced arsenic removal: Mechanism, toxicity and performance in complicated water matrices - Shiqi Tian; Yuwei Ma; Yuanyuan Xu; Yingzi Lin; Jun Ma; Gang Wen (Water Research, 2024)

Amplified photosynthetic responses to drought events offset the positive effects of warming on arid desert plants - Yuwei Lin; Ting Xie; Shuanglang Li; Xinrong Li; Wenjing Liu (Science of The Total Environment, 2024)

Cyclic di-GMP incorporates the transcriptional factor FleQ03 in Pseudomonas syringae MB03 to elicit biofilm-dependent resistance in response to Caenorhabditis elegans predation - Xiaowen Sun; Fan Xiao; Yuwei Su; Zhi Li; Xun Yu; Rebecca E. Parales; Lin Li (Journal of Invertebrate Pathology, 2024)

Thermal transformations of perfluorooctanoic acid (PFOA): Mechanisms, volatile organofluorine emissions, and implications to thermal regeneration of granular activated carbon - Junli Wang; Lillian N. Tran; Jose Mendoza; Kunpeng Chen; Linhui Tian; Yuwei Zhao; Jinyong Liu; Ying-Hsuan Lin (Journal of Hazardous Materials, 2024)

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

DOTAD: A Database of Therapeutic Antibody Developability - Wenzhen Li; Hongyan Lin; Ziru Huang; Shiyang Xie; Yuwei Zhou; Rong Gong; Qianhu Jiang; ChangCheng Xiang; Jian Huang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Integrated transcriptomic and metabolomic analyses revealed the effect of melatonin on delaying persimmon fruit softening - Yuwei Wang; Shiyu Lin; Mengyuan Zhang; Jiaojiao Nie; Aijun Tang; Ningjing Sun; Shuyu Zeng; Xiaofen Liu; Yuduan Ding; Xueren Yin; Qinggang Zhu (Postharvest Biology and Technology, 2024)

Northward expansion of the West Kunlun orogenic belt during the Cenozoic and its implications for the evolution of the northwest Tibetan Plateau: Constraints from sediment dispersal patterns in the Buya Basin, China - Shujun Liang; Xiubin Lin; Chunyang Li; Xiaochun Wei; Yang Qu; Kaixuan An; Cai Chen; Xianzhang Yang; Yong Li; Liang Zhang; Jiangwei Shang; Li Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Corrosion performance of A3 carbon steel in 30wt.% MEA and AMP-MEA blends for post-combustion carbon capture: Effect and mechanism of corrosion inhibitors - Yuwei Wang; Mengxiang Fang; Jun Gao; Chao Li; Yan Huang; Lin Yang; Shuifei Li; Ximing Hu; Tao Wang (International Journal of Greenhouse Gas Control, 2024)

Genome-wide identification of the SAUR gene family and screening for SmSAURs involved in root development in Salvia miltiorrhiza - Wei Wang; Yuwei Zheng; Lin Qiu; Dongfeng Yang; Ziyang Zhao; Yuanyuan Gao; Ru Meng; Hongguang Zhao; Shuncang Zhang (Plant Cell Reports, 2024)

Machine Learning Analysis of Impact of Western US Fires on Central US Hailstorms - Xinming Lin; Jiwen Fan; Yuwei Zhang; Z. Jason Hou (Advances in Atmospheric Sciences, 2024)

A vertical-flow constructed wetland–microalgal membrane photobioreactor integrated system for treating high-pollution-load marine aquaculture wastewater: A lab-scale study - Lin Zhao; Jun Tang; Yuwei Xu; Yifan Zhang; Zihao Song; Guiping Fu; Zhangli Hu (Science of The Total Environment, 2024)

Exploring the electron transfer regime occurring in peroxides activation by graphite: Origin, mechanism and efficiency in complicated water matrices - Shiqi Tian; Yuanyuan Xu; Yuwei Ma; Susu Jiang; Jun Ma; Yingzi Lin; Gang Wen (Chemical Engineering Journal, 2024)

The Characteristics of Degradation of Enrofloxacin by Vis / BC-BiOI / PMS Photocatalytic System Based on BiOI-Modified Biochar - Yutong Xiang; Bin Tan; Meng Li; Yuning Liu; Xiangyu Liu; Yuwei Ding; Bing Lin; Qian Zhang (Water, Air, & Soil Pollution, 2024)

Risk of papillary thyroid carcinoma and nodular goiter associated with exposure to semi-volatile organic compounds: A multi-pollutant assessment based on machine learning algorithms - Fei Wang; Yuanxin Lin; Jianing Xu; Fugui Wei; Simei Huang; Shifeng Wen; Huijiao Zhou; Yuwei Jiang; Haoyu Wang; Wenlong Ling; Xiangzhi Li; Xiaobo Yang (Science of The Total Environment, 2024)

Influence of atmospheric circulation on the stable isotope of precipitation in the monsoon margin region - Siyu Lu; Guofeng Zhu; Gaojia Meng; Xinrui Lin; Yuwei Liu; Dongdong Qiu; Yuanxiao Xu; Qinqin Wang; Longhu Chen; Rui Li; Yinying Jiao (Atmospheric Research, 2024)

Harnessing diurnal dynamics: Deciphering the interplay of light cycles on algal-bacterial membrane bioreactors - Sihan Cheng; Yuwei Zhang; Yu Zhao; Xin Hu; Hongjun Lin; Jiaheng Teng; Meijia Zhang (Science of The Total Environment, 2024)

SmTIR1 positively regulates the growth and root development of Salvia miltiorrhiza - Lin Qiu; Yuwei Zheng; Wei Wang; Lei Zhang; Ziyang Zhao; Yuanyuan Gao; Dongfeng Yang; Shuncang Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Soil erosion sensitivity and prediction for hilly areas of Hubei Province, China, using combined RUSLE and LSTM models - Yaodong Ping; Pei Tian; Li Luo; Yahui Guo; Yuwei Gong; Zhanliang Zhu; Yongsheng Cui; Lin Chen (Journal of Soils and Sediments, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Fe2O3 nanosheet sacrificed templates for highly-permeable hollow fiber ultrafiltration membranes - Yuwei He; Chong Li; Zhen Lin; Qiugen Zhang (Chemical Engineering Journal, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

The cellular trajectories of tumor-associated macrophages decipher the heterogeneity of pancreatic cancer - Jiajing Lin; Fengchun Lu; Yuwei Wu; Heguang Huang; Yu Pan (Functional & Integrative Genomics, 2023)

Exploring the Therapeutic Effects and Mechanisms of Transcranial Alternating Current Stimulation on Improving Walking Ability in Stroke Patients via Modulating Cerebellar Gamma Frequency Band—a Narrative Review - Tingyi Feng; Lichao Zhang; Yuwei Wu; Lin Tang; Xixi Chen; Yuanli Li; Chunlei Shan (The Cerebellum, 2023)
The cerebellum plays an important role in maintaining balance, posture control, muscle tone, and lower limb coordination in healthy individuals and stroke patients. At the same time, the relationship between cerebellum and motor learning has been widely concerned in recent years. Due to the relatively intact structure preservation and high plasticity after supratentorial stroke, non-invasive neuromodulation targeting the cerebellum is increasingly used to treat abnormal gait in stroke patients. The gamma frequency of transcranial alternating current stimulation (tACS) is commonly used to improve motor learning. It is an essential endogenous EEG oscillation in the gamma range during the swing phase, and rhythmic movement changes in the gait cycle. However, the effect of cerebellar tACS in the gamma frequency band on balance and walking after stroke remains unknown and requires further investigation.

Optimizing aeration intensity to enhance self-flocculation in algal-bacterial symbiosis systems - Jiahui Huang; Sihan Cheng; Yuwei Zhang; Jiaheng Teng; Meijia Zhang; Hongjun Lin (Chemosphere, 2023)

Melamine-Ag with dual functions of electrochemiluminescence luminophore and coreactant accelerators: Construction of MIP/M-Ag@MoS2-QDs sensing platform for specific detection of thiabendazole - Haiyang Wang; Lin Cai; Wen Hao; Yuwei Wang; Guozhen Fang; Shuo Wang (Food Chemistry, 2023)

Heavy metals transport patterns and risk evaluation in the pig manure- black soldier fly-tilapia food chain - Changquan Lin; Xiting Xia; Yuwei Li; Rong Ma; Langping Zhu; Xiaotian Li; Youqian Tang; Chunming Wang (Environmental Pollution, 2023)

IKBKE regulates angiogenesis by modulating VEGF expression and secretion in glioblastoma - Lin Zhu; Gaochao Guo; Yuwei Jin; Aixia Hu; Yang Liu (Tissue and Cell, 2023)

Enhanced methane yield in anaerobic digestion of waste activated sludge by combined pretreatment with fungal mash and free nitrous acid - Min Zhang; Yuwei Yang; Huaqian Mou; Aodong Pan; Xiaomei Su; Jianrong Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2023)

Water use strategy of nitraria tangutorum shrubs in ecological water delivery area of the lower inland river: Based on stable isotope data - Dongdong Qiu; Guofeng Zhu; Mohd Aadil Bhat; Lei Wang; Yuwei Liu; Liyuan Sang; Xinrui Lin; Wenhao Zhang; Niu Sun (Journal of Hydrology, 2023)

Emulsions containing composite (clove, oregano, and cinnamon) essential oils: Phase inversion preparation, physicochemical properties and antibacterial mechanism - Jiajie Hu; Hangxin Zhu; Yuwei Feng; Mijia Yu; Yueqiang Xu; Yadong Zhao; Bin Zheng; Jiheng Lin; Wenhua Miao; Rusen Zhou; Patrick J. Cullen (Food Chemistry, 2023)

Carboxymethyl chitosan/sodium alginate hydrogel films with good biocompatibility and reproducibility by in situ ultra-fast crosslinking for efficient preservation of strawberry - Yuwei Zhang; Wenxin Zhao; Zhenhao Lin; Zhongfeng Tang; Baofeng Lin (Carbohydrate Polymers, 2023)

Comparative transcriptome analysis reveals the regulatory effects of exogenous auxin on lateral root development and tanshinone accumulation in Salvia miltiorrhiza - Shuncang Zhang; Lin Qiu; Yuwei Zheng; Wei Wang; Hongguang Zhao; Dongfeng Yang (Planta, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Horseradish peroxidase (HRP) and glucose oxidase (GOX) based dual-enzyme system: Sustainable release of H2O2 and its effect on the desirable ping pong bibi degradation mechanism - Xiangyu Liu; Qian Zhang; Meng Li; Song Qin; Ziqi Zhao; Bing Lin; Yuwei Ding; Yutong Xiang; Chengwei Li (Environmental Research, 2023)

A comparison between Pixel-based deep learning and Object-based image analysis (OBIA) for individual detection of cabbage plants based on UAV Visible-light images - Zhangxi Ye; Kaile Yang; Yuwei Lin; Shijie Guo; Yiming Sun; Xunlong Chen; Riwen Lai; Houxi Zhang (Computers and Electronics in Agriculture, 2023)

The isotopes of precipitation have climate change signal in arid Central Asia - Guofeng Zhu; Yuwei Liu; Lei Wang; Liyuan Sang; Kailiang Zhao; Zhuanxia Zhang; Xinrui Lin; Dongdong Qiu (Global and Planetary Change, 2023)

Comparative Transcriptomes Reveal the Mitigation Effect of GR24 in Alfalfa Under Drought Stress - Yuwei Yang; Mingzhou Gu; Jiamin Chen; Rongle Zhang; Zhiyuan Liu; Yanhua Shi; Dalin Liu; Lin Wang (Journal of Plant Growth Regulation, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Hybridization of carboxymethyl chitosan with bimetallic MOFs to construct renewable metal ion “warehouses” with rapid sterilization and long-term antibacterial effects - Hao Li; Yuwei Zhang; Yuancheng Zhang; Fuxiang Wei; Yongfu Deng; Zhenhao Lin; Chuanhui Xu; Lihua Fu; Baofeng Lin (Carbohydrate Polymers, 2023)

Inheritance and Development: The Evolution and Overview of China’s Fisheries Legal System - Wei Wu; Yang Liu; Zhaobin Pei; Yan Lin; Xin Sun; Jiaqi Xing; Yuwei Wang; Yu Liu (Fishes, 2022)
China’s legal system governing fisheries in China has been stable during development. In line with China’s national conditions and the spirit of the times, they have adhered to the concept of green development and maintaining the sustainable development of fishery production activities. Studying the history of Chinese fishery law is beneficial for the world to understand the evolution of this legislation and is a better gateway for the world to understand fisheries law with Chinese characteristics. Fishery, in this context, refers to fishing and fish farming. In China, fisheries are under the management of the Ministry of Agriculture and Rural Affairs, while fisheries enforcement has a special law enforcement department for collaborative management. Therefore, both fishing and fish farming in China’s fisheries industry belong to the category of agriculture. This is different from the West and is precisely what makes China unique. This paper explores the Chinese fishery legal and general legal systems by investigating policy guidelines, laws, and regulations on China’s fishery industry since 1949. Furthermore, it analyzes the development process of fisheries. Organizing the development status of China’s fishery legal and regulatory system analyzes the problems of fishery production control and development, searches for paths and methods to solve the practical problems, and finally, makes a reasonable outlook on the development prospect of China’s fishery.

RsmA3 modulates RpoS through the RetS‐Gac‐Rsm signalling pathway in response to H 2 O 2 stress in the phytopathogen Pseudomonas syringae - Xun Yu; Cui Meng; Xiaocheng Tan; Yuwei Su; Zhiping Cao; Tzann‐Shun Hwang; Lin Li (Environmental Microbiology, 2022)
Reactive oxygen species are a fatal challenge to the plant pathogenic bacterium Pseudomonas syringae . In this study, we reveal that the global regulatory protein RsmA3 from the RetS‐Gac/Rsm signalling pathway modulates RpoS in the early‐log growth phase in the P . syringae wild‐type strain MB03, thereby regulating oxidative tolerance to H 2 O 2 and ultimately affecting pathogenicity to the host plant. Following increased H 2 O 2 by external addition or endogenous induction by menadione, the resistance of the mutant strain Δ retS to H 2 O 2 is significantly enhanced due to rapid increases in the transcription of Rsm‐related non‐coding small RNAs (nc sRNAs), a sigma factor RpoS, and H 2 O 2 ‐detoxifying enzymes. Moreover, the Δ retS mutant is significantly less pathogenic in cucumber leaves. Seven Rsm‐related nc sRNAs (namely, rsmZ , rsmY and rsmX 1–5 ) show functional redundancy in the RetS‐Gac‐Rsm signalling pathway. External addition of H 2 O 2 stimulates increases in the transcription of both rsmY and rsmZ . Thus, we propose a regulatory model of the RetS‐Gac‐Rsm signalling pathway in P . syringae MB03 for the regulation of H 2 O 2 tolerance and phytopathogenicity in the host plant.

Effects of agricultural activities on hydrochemistry in the Shiyang River Basin, China - Wenhao Zhang; Guofeng Zhu; Dongdong Qiu; Yuwei Liu; Liyuan Sang; Xinrui Lin; Huiying Ma; Kailiang Zhao; Yuanxiao Xu (Environmental Science and Pollution Research, 2022)

The geochemical behavior of trace metals and nutrients in submerged sediments of the Three Gorges Reservoir and a critical review on risk assessment methods - Bin Wang; Shu Chen; Yuwei Chen; Nelson Belzile; Rui Zheng; Yuankun Yang; Kaibin Fu; Yongcan Chen; Binliang Lin; Zhaowei Liu; Jian Sun (Environmental Science and Pollution Research, 2021)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Uncertainty Analysis of Ship Model Propulsion Test on Actual Seas Based on Monte Carlo Method - Guangli Zhou; Yuwei Wang; Dagang Zhao; Jianfeng Lin (Journal of Marine Science and Engineering, 2020)
As a new testing technology, large-scale ship model tests on the sea are advantageous in addressing the scale effect in ship models and in simulating ship navigation conditions. In this study, the uncertainty of a ship model propulsion test on the sea was analyzed using the Monte Carlo method, and the influence of the test environment was quantified. We used a 25 m-long ship model for the propulsion performance test. Based on the procedure recommended by the International Standardization Organization (ISO), several tests were conducted on the Yellow Sea (the northwestern part of the East China Sea). The results demonstrate that the wind and waves in the environment are the two factors that have the greatest influence on the test accuracy. This study will aid the development of sea trials, and the analysis method used in the propulsion test is also suitable for many complex ship tests.

Co-Delivery of Ciprofloxacin and Colistin in Liposomal Formulations with Enhanced In Vitro Antimicrobial Activities against Multidrug Resistant Pseudomonas aeruginosa - Shaoning Wang; Shihui Yu; Yuwei Lin; Peizhi Zou; Guihong Chai; Heidi H. Yu; Hasini Wickremasinghe; Nivedita Shetty; Junhong Ling; Jian Li; Qi Zhou (Pharmaceutical Research, 2018)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Overexpression of a maize WRKY58 gene enhances drought and salt tolerance in transgenic rice - Ronghao Cai; Yang Zhao; Yufu Wang; Yongxiang Lin; Xiaojian Peng; Qian Li; Yuwei Chang; Haiyang Jiang; Yan Xiang; Beijiu Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)